Development of Sasirangan Science Literacy Media as Local Wisdom Strengthening the Pillars of UIN Antasari's Scientific Philosophy - Wicaksono, Ardian Trio; Rahman, Viandri Mulia (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2026)
The purpose of this study was to determine the design process, validity, and student responses regarding the development of sasirangan science literacy-based learning media as a local wisdom to strengthen the philosophical pillars of UIN Antasari. The research subjects were sasirangan artisans, active students of the science education study program. The research was conducted in Banjar Regency and at Campus 2 of UIN Antasari Banjarmasin. The 4D development model was used. Data were obtained through interviews, literature studies, questionnaires, and observations, processed using descriptive analysis. Research results: (1) The media design process discusses the identification of development objectives, target audience, learning context, creation of interview and observation instrument grids, and creation of initial learning media designs, (2) The results of the validation by material experts were 81.42% in the very valid category and the results of the validation by media experts were 80% in the valid category, (3) Student responses at the very appropriate level with positive comments.